2012
DOI: 10.3389/fcimb.2012.00073
|View full text |Cite
|
Sign up to set email alerts
|

MiR-155 Induction by Microbes/Microbial Ligands Requires NF-κB-Dependent de novo Protein Synthesis

Abstract: MiR-155 regulates numerous aspects of innate and adaptive immune function. This miR is induced in response to Toll-like receptor ligands, cytokines, and microbial infection. We have previously shown that miR-155 is induced in monocytes/macrophages infected with Francisella tularensis and suppresses expression of the inositol phosphatase SHIP to enhance activation of the PI3K/Akt pathway, which in turn promotes favorable responses for the host. Here we examined how miR-155 expression is regulated during infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 49 publications
1
25
1
Order By: Relevance
“…It remains to be determined whether GPCRs also influence the expression or activation of enzymes involved in the microRNA machinery. A variety of transcription factors have been implicated in microRNA generation, such as NFκB (40), Egr (41, 42) and AP-1 (27, 43-46). We further investigated whether LTB 4 /BLT1 could enhance the generation of microRNAs by controlling activation of AP-1 since this transcription factor is responsible for the expression of miR-155 and also miR-146b (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be determined whether GPCRs also influence the expression or activation of enzymes involved in the microRNA machinery. A variety of transcription factors have been implicated in microRNA generation, such as NFκB (40), Egr (41, 42) and AP-1 (27, 43-46). We further investigated whether LTB 4 /BLT1 could enhance the generation of microRNAs by controlling activation of AP-1 since this transcription factor is responsible for the expression of miR-155 and also miR-146b (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs regulate intracellular pathways of numerous inflammatory mediators [16] and their role in the regulation of immune responses has been widely documented, including the presence of miR-181a in the thymus and miR-223 in the bone marrow being implicated in the differentiation of pluripotent hematopoietic stem cells [17,18]. Additionally, miR-155 has been shown to be induced by viral and bacterial pathogens, as well as inflammatory cytokines, suggesting it to be a component of the innate immune response [19,20]. Even though the function of these novel regulators in several processes is now well described, their effect on the JAK-STAT pathway has not been explored in any great detail.…”
Section: Introductionmentioning
confidence: 99%
“…Among several inflammatory and oncogenic microRNAs, microRNA-155 (miR-155) has been recently identified as an NF-κB-dependent microRNA, involving in the development of inflammation, immune responses, and cancers [5,6,11,25]. In this context, Wang et al have reported both miR-155 overexpression and NF-кB activation at the early stages of choline-deficient and amino acid-defined diet-induced hepatocarcinogenesis mouse model [27].…”
mentioning
confidence: 99%